DESAIN KURIKULUM PROGRAM TAHFIDZUL QUR’AN BERBASIS KEARIFAN LOKAL - Hefniy Hefniy; Raudatul Jannah (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2019)
This paper discusses the Curriculum Design of the Local Wisdom-based Tahfidzul Qur’an Program. The purpose of this study was to determine the curriculum planning of the Tahfidzul Qur'an program at Ibnu Kathir Islamic Boarding School in Jember. Memorizing the Qur'an is one of the strategies in instilling educational goals in Indonesia. The soul that is awakened in the memory of the Qur'an will feel peaceful. And they are classified as good human beings. How better, if humans continue to study, understand, read and memorize them in order to practice them in everyday life. Therefore, the contents of the Qur'an are not in doubt in building human character. The Qur'an is a combination of tahfidz and the Qur'an. The Qur'an is the word of God revealed to the Prophet Muhammad, written in the Manuscripts, moved regularly according to history, as well as readings including worship as a guide in human life.